A clinical study of sudden deafness. (October 2015) - Zhang, Xiaotong; Xu, Xinda; Ma, Weijun; Zhang, Qing; Tong, Busheng; Yu, Hong; Xu, Min; Ren, Tianying; Rosenhall, Ulf; Anniko, Matti; Duan, Maoli
Abstract Conclusions: Sudden Sensorineural Hearing Loss (SSHL) was commonly seen in middle aged people. Tinnitus was reported by 87.2% of the patients, and dizziness or vertigo were reported by 48.5%. The most common concomitant disorder of SSHL was hyperlipidemia. Objective: A retrospective register study with SSHL was performed in Xi'an, China, from 2000–2009. Results: Of 617 inpatients, the right ear was affected in 267 cases, the left ears in 282 cases, and both ears in 68 cases. The most common age of patients was 41–50 years. There were 20.4% SSHL patients with hypertension, coronary artery disease, or diabetes, and 49.6% patients with hyperlipidemia. Auditory Brainstem Responses (ABR) were performed in 460 patients (504 ears) before treatment, and the ABR threshold of 56.4% ears was > 90 dB. The constituent ratio of patients with an ABR threshold over 90 dB was greater in the vertigo group than the other group. CT and/or MRI scans were available in 277 cases, of which 40 cases (14.4%) were abnormal.